2018
DOI: 10.1002/cam4.1592
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aberrant expression and genetic polymorphisms of Rad21 on cervical cancer biology

Abstract: The therapeutic challenge of advanced, recurrent, and refractory cervical cancer (CC) needs to develop new molecularly targeted drugs. Rad21 is an important regulatory gene that maintains the correct dissociation of sister chromatids during cell mitosis. The aim of this study was to investigate the effect of Rad21 on CC. Rad21 expression in CC and cervical intraepithelial neoplasia III was significantly increased. Women with the rs2289937 C genotype (CC+CT) of rs4570 and rs4579555 genotypes and haplotype 1 (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Previous study identified RAD21 as a new binding partner of mutant P53 in ovarian cancer, the specific molecular mechanism by which RAD21 regulates the expression of MFAP2 and the relationship to mutant p53 in HCC remains to be investigated. 23 , 17 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Previous study identified RAD21 as a new binding partner of mutant P53 in ovarian cancer, the specific molecular mechanism by which RAD21 regulates the expression of MFAP2 and the relationship to mutant p53 in HCC remains to be investigated. 23 , 17 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high RAD21 expression in patients with cervical cancer was associated with poor disease survival and involving the development of cervical cancer possibly by participating in the regulation of cell cycle and the nuclear output of the tumor suppressor gene. 17 Deb et al 18 conducted a retrospective study of 652 patients with colon cancer and found that RAD21 expression is related to disease progression, showing a positive correlation with chemotherapy in tumors harboring KRAS mutations and resistance. In breast cancer, Xu et al 19 showed that RAD21 expression correlated with early relapse.…”
Section: Discussionmentioning
confidence: 99%
“…upregulates cell proliferation and downregulates p53 signaling [43] . In this study, we found that RAD21 and SMC3 served downstream of Wnt/β-catenin signaling and directly enhanced CENPK transcription.…”
Section: Discussionmentioning
confidence: 99%